STRATEGI PEMERINTAH DESA DALAM PEMBANGUNAN INSFRASTRUKTUR DI DESA KERTAMUKTI KECAMATAN CIBITUNG KABUPATEN BEKASI - Haloho, Putri Esther; Purnamasari, Hanny; Aryani, Lina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Infrastructure development in Bekasi Regency is important because people's lives cannot be separated from the need for adequate infrastructure. Infrastructure is a physical facility and its services that are provided to support the work of the socio- economic system so that it becomes more functional for businesses to meet the needs of various problems. Infrastructure development in Kertamukti Village, Cibitung District, Bekasi Regency is important to increase the independence and economy of the villagers. Building village infrastructure is not just building roads and gates. The main reason for the procurement of village infrastructure is the lack of main facilities and infrastructure in the village. These limitations make it difficult for villages to develop. Villages are usually dominated by agrarian areas where some of the residents work as farmers. Often infrastructure development encounters obstacles, especially the limited public access to development policy making by the Government. The purpose of this study was to determine the Village Government's Strategy in Increasing Infrastructure Development in Kertamukti Village, Cibitung District, Bekasi Regency by using Salusu theory.